Oxygen Contamination of Multilayer TiNx — SiO2 — Si Structures found by Resonant RBS Analysis - Aslanoglou, X. A.; Evangelou, E.; Konofaos, N.; Dimitriades, Ch.; Kossionides, E.; Kaliampakos, G.; Kriembardis, G. (HNPS Advances in Nuclear Physics, 2020)
Multi layer structures consisting of TiN — SÌO2 — Si layers operating as MOS devices were constructed and tested for their electrical properties. RBS and resonance reaction analysis were performed for the characterisation of the structure of the devices. The results show a correlation between the structure found by RBS and the electrical performance of the devices.